Эмбриональное развитие паразитического клеща Varroa jacobsoni (Mesostigmata, Varroidae) - Акимов, И.А.; Ястребцов, А.В. (Вестник зоологии, 1988)
A detailed description of the oocytes ripening processes, blastulation, gastrulation and organogenesis is presented. Organogenetic process is divided in four essential stages: early tissues differentiation, prelarval morphogenesis, larval morphogenesis, protonymphal morphogenesis. Histogenesis processes are shown for each of these stages: somite formation, gnathemization, differentiation of principal parts of different organic systems. appendages topography (especiiallv IV pair of legs). Oviposition takes place at the final stages of the protonympha I morphogenesis. Eggs deposited earlier are found to be not vital. Centroleci tal eggs, superficial division and remarkable organogenesis velocity are characteristic of V. jacobsoni. No pronounced blastokinetic processes have been observed.